6.4 Transfusion management and haemostatic changes in major obstetric haemorrhage in the UK. (9th June 2014) - Green, L; Knight, M; Seeney, FM; Collins, PW; Collis, RE; Hopkinson, CL; Stanworth, SJ
Abstract : Blood transfusion is fundamental to improving outcomes during major obstetric haemorrhage (MOH). Current guidelines recommend that fresh frozen plasma (FFP), cryoprecipitate and platelets are transfused when PT/APTT is >1.5 × baseline, fibrinogen <1 g/dL and platelet count <50 × 10 9 /L, respectively. However, these recommendations are not evidence-based. Aims: to describe coagulation abnormalities and transfusion requirements during MOH (defined as transfusion of ≥8 units of RBC within 24 hrs of delivery). Methods: Cases were identified using the UK Obstetric Surveillance System, between July 2012 and June 2013. Results: We identified 181 cases; 68% delivered by caesarean. The median estimated blood loss was 6000 mL (IQR: 4500–8000). The main causes for MOH were uterine atony (40%) and placenta accreta/increta/percreta (16%). The median (IQR) platelet count, APTT-ratio and fibrinogen (worst values) were 68 x 10 9 /L (50–95), 1.3 (1.0–1.9) and 1.4 (0.8–2.2) respectively. In 33%, 27% and 25% of cases APTT-ratio was >1.5x baseline, fibrinogen <1.0 g/dL and platelet <50 × 10 9 /L respectively. FFP, cryoprecipitate and platelets were transfused in 99%, 61% and 77% of women. The median (IQR) RBC, FFP and cryoprecipitate transfused were: 10 (8–1), 6 (4–8), and 2 units (2–4), with the first FFP and cryoprecipitate transfused after a median of 4 (3–6) and 7 RBC units (6–9) respectively. 45% of women underwent hysterectomy, 2 died, 82% were admitted to ITU/HDU, and 28% developed additional major morbidity. Conclusion: Guideline criteria for plasma/platelet transfusion were fulfilled in only 25% of these severe cases, indicating that further research is needed to define transfusion triggers in MOH.